T-cadherin Expressing Cells in the Stromal Vascular Fraction of Human Adipose Tissue: Role in Osteogenesis and Angiogenesis. (8th March 2022) - Guerrero, Julien; Dasen, Boris; Frismantiene, Agne; Pigeot, Sebastien; Ismail, Tarek; Schaefer, Dirk J; Philippova, Maria; Resink, Therese J; Martin, Ivan; Scherberich, Arnaud
Abstract: Cells of the stromal vascular fraction (SVF) of human adipose tissue have the capacity to generate osteogenic grafts with intrinsic vasculogenic properties. However, cultured adipose-derived stromal cells (ASCs), even after minimal monolayer expansion, lose osteogenic capacity in vivo. Communication between endothelial and stromal/mesenchymal cell lineages has been suggested to improve bone formation and vascularization by engineered tissues. Here, we investigated the specific role of a subpopulation of SVF cells positive for T-cadherin (T-cad), a putative endothelial marker. We found that maintenance during monolayer expansion of a T-cad-positive cell population, composed of endothelial lineage cells (ECs), is mandatory to preserve the osteogenic capacity of SVF cells in vivo and strongly supports their vasculogenic properties. Depletion of T-cad-positive cells from the SVF totally impaired bone formation in vivo and strongly reduced vascularization by SVF cells in association with decreased VEGF and Adiponectin expression. The osteogenic potential of T-cad-depleted SVF cells was fully rescued by co-culture with ECs from a human umbilical vein (HUVECs), constitutively expressing T-cad. Ectopic expression of T-cad in ASCs stimulated mineralization in vitro but failed to rescue osteogenic potential in vivo, indicating that the endothelial nature of the T-cad-positive cells is the key factor for induction of osteogenesis in engineered grafts based on SVF cells. This study demonstrates that crosstalk between stromal and T-cad expressing endothelial cells within adipose tissue critically regulates osteogenesis, with VEGF and adiponectin as associated molecular mediators. Graphical Abstract: